Feeding European sea bass (Dicentrarchus labrax) juveniles with a functional synbiotic additive (mannan oligosaccharides and Pediococcus acidilactici): An effective tool to reduce low fishmeal and fish oil gut health effects?. Issue 81 (October 2018) - Torrecillas, S.; Rivero-Ramírez, F.; Izquierdo, M.S.; Caballero, M.J.; Makol, A.; Suarez-Bregua, P.; Fernández-Montero, A.; Rotllant, J.; Montero, D.
Abstract: The aim of this study was to assess the effects of dietary mannan oligosaccharides (MOS), Pediococcus acidilactici or their conjunction as a synbiotic in low fish meal (FM) and fish oil (FO) based diets on European sea bass ( Dicentrarchus labrax ) disease resistance and gut health. For that purpose, sea bass juveniles were fed one of 6 diets containing different combinations of MOS (Biomos ® and Actigen © ; Alltech, Inc., Kentucky, USA) and Pediococcus acidilactici (BAC, Bactocell ® ; Lallemand Inc., Cardiff, UK) replacing standard carbohydrates as follows (MOS (%)/BAC (commercial recommendation): high prebiotic level (HP) = 0.6/0, low prebiotic level (LP) = 0.3/0, only probiotic (B) = 0/+, high prebiotic level plus probiotic (HPB) = 0.6/+, low prebiotic level plus probiotic (LPB) = 0.3/+, control (C) = 0/0 for 90 days. After 60 and 90 days of feeding trial, fish were subjected to an experimental infection against Vibrio anguillarum . Additionally, inducible nitric oxide synthase (iNOS) and tumor necrosis factor α (TNFα) gut patterns of immunopositivity and major histocompatibility complex class II (MHCII), transforming growth factor β (TGF-β), regulatory T-cell subset (CD4 + T lymphocytes) and effector T cell (CD8α + T lymphocytes) gene expression patterns in gut by in situ hybridization were evaluated after 90 days of feeding. The effects of both additives on posterior gut through Gut Associated Lymphoid Tissue (GALT) gene expression was also studied. Fish fed the prebiotic and its combination with P. acidilactici presented increased weight regardless of the dose supplemented after 90 days of feeding, however no effect was detected on somatic indexes. For posterior gut, morphometric patterns and goblet cells density was not affected by MOS, P. acidilactici or its combination. Anti-iNOS and anti-TNFα gut immunopositivity patterns were mainly influenced by MOS supplementation and not by its combination with P. acidilactici . MHCII-β, TCR-β, CD4 and CD8-α positive cells distribution and incidence was not affected by diet. Fish fed HP dose presented a clear up-regulation of TNF-α, cyclooxygenase-2 (COX-2), CD4 and IL10, whereas P. acidilactici dietary supplementation increased the number of interleukin-1β (IL1β) and COX-2 gene transcripts. Synbiotic supplementation resulted in a reduction of MOS-induced gut humoral proinflammatory response by increasing the expression of some cellular-immune system related genes. Fish mortality after V. anguillarum infection was reduced in fish fed LPB and LP diets compared to fish fed the non-suppelmented diet after 90 days of feeding. Thus, overall pointing to the combination of a low dose of MOS and P. acidilactici as synbiont (LPB) as a viable tool to potentiate European sea bass juvenile's growth and disease resistance when supplemented in low FM and FO diets. Highlights: Dietary MOS and its combination with P. acidilactici promotes growth performance. The dietary combination of low prebiotic dose MOS and P. acidilactici increase the density of posterior gut goblet cells. MOS dietary dose is a determining factor in terms of the gut proinflammatory pattern of response. P. acidilactici helps fish to reach gut intestinal homeostasis after fed fish with low FM and FO diets. Dietary MOS and its combination with P. acidilactici increase fish disease resistance against V. anguillarum.